Sr-site cation substitution effects on formation and superconductivity of (TI,Bi)Sr₂(Ca,Y)Cu₂O₇ ceramics / Baktiar Musa - Musa, Baktiar (2005)
In thi s work , elemental substitution was employed to stabilize the 1212-phase durin g the synthesis of TISr₂Ca Cu₂O₇ superconductors. Although previously thi s practice was mostly carried out at the TI and Ca sites, another metallic site i.e. the Sr-site can also be equally important in stabilizing the 1212-phase…